CCS STAFF ASSIGNMENTS (Tufts Archival Research Center, 2007)
Memo to the directors of Californians for Common Sense (CCS) from Woodward & McDowell regarding CCS staff assignments. Names different positions and lists responsibilities. Lists present staff members and their responsibilities.